A MORPHO-SEMANTIC ANALYSIS OF COMPOUND NOUNS IN A. D. MALEDU’S SEPEDI DOCTORAL THESIS - Seanego, James (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Noun compounding is a linguistic process involving the combination of two or more lexical items to form a single noun. This method of word formation is effectively demonstrated in the translated Sepedi Bible as well as in translations of other African languages. This article seeks to critically assess the innovative use of compound nouns as observed in A.D. Maledu’s doctoral thesis, which is written in Sepedi—one of South Africa’s twelve official languages. Maledu’s body of scholarly work is recognised for its prolific and distinctive use of compound nouns, showcasing a rare form of linguistic creativity in African-language scholarship. The article intensively assesses these compound nouns and explores their potential utility for Sepedi language custodians. Employing a qualitative research approach, the study primarily used document review as the data collection method. Out of the pool of compound nouns used in the thesis, only thirty-four (34) were purposively sampled for discussion. The findings were analysed thematically, thereby situating the study within a thematic framework. The analysis reveals that most of the compound nouns applied in the thesis are endocentric and copulative compounds, with minimal exocentric examples. Ultimately, the article commends the thesis author’s inventive contribution to the development of compound nouns, thus enriches the corpus of Sepedi applied linguistics in the digital era and beyond.